Ultrafast Study of Interfacial Charge Transfer Mechanism in Assembled Systems of CsPbBr3 and Titanium Dioxide: Size Effect of CsPbBr3 - Ying Lv; Menghan Duan; Jie An; Yunpeng Wang; Luchao Du (Nanomaterials)
Lead halide perovskite quantum dots, also known as perovskite nanocrystals, are considered one of the most promising photovoltaic materials for solar cells due to their outstanding optoelectronic properties and simple preparation techniques. The key factors restricting the photoelectric conversion efficiency of solar cell systems are the separation and transmission performances of charge carriers. Here, femtosecond time-resolved ultrafast spectroscopy was used to measure the interfacial charge transfer dynamics of different sizes of CsPbBr3 assembled with TiO2. The effect of perovskite size on the charge transfer is discussed. According to our experimental data analysis, the time constants of the interfacial electron transfer and charge recombination of the assembled systems of CsPbBr3 and titanium dioxide become larger when the size of the CsPbBr3 nanocrystals increases. We discuss the physical mechanism by which the size of perovskites affects the rate of charge transfer in detail. We expect that our experimental results provide experimental support for the application of novel quantum dots for solar cell materials.